Weighted spaces of holomorphic functions on the upper halfplane - Ardalani, Mohammad Ali; Lusky, Wolfgang (MATHEMATICA SCANDINAVICA, 2012)
We discuss weighted spaces Hv(G) of holomorphic functions on the upper halfplane G where v(w) = v(i Im w), w G, _t→ 0 v(it)=0 and v(it) is increasing in t. We characterize those weights v with moderate growth where Hv(G) is isomorphic to l_∞ and we show that this is never the case if v is bounded.